Selective Co‐Assembly of Water‐Soluble Conjugated Polyelectrolyte with Discernable Fluorescence Modulation for Antibiotic Detection - Hyena Ji; Yesica Fernanda Florez‐Villabona; Youngsun Kim; Yerim Kim; Yongju Kim; Seungyun Baik; Young Hun Seo; Sehoon Kim (Advanced Sensor Research)
Abstract Residual antibiotics threaten ecosystems and public health by fostering antibiotic resistance and water contamination. To address this, PQx‐Ph, a water‐soluble conjugated polyelectrolyte, is developed as a selective fluorescent probe for antibiotic detection. The sulfonate‐functionalized architecture of PQx‐Ph facilitates the molecular co‐assembly with antibiotics, resulting in fluorescence responses through antibiotic‐selective distinct mechanisms, i.e., aggregation‐induced emission (AIE) and twisted intramolecular charge transfer (TICT). These antibiotic‐selective mechanisms enable 1) fluorescence quenching upon co‐assembly with kanamycin (KAN) due to electrostatic binding and 2) fluorescence enhancement upon co‐assembly with erythromycin (ERY) through hydrophobic interactions and TICT stabilization. PQx‐Ph exhibits remarkable selectivity toward KAN, demonstrating strong binding with minimal interference from various competing substances. PQx‐Ph exhibits matrix‐dependent sensing performance, achieving nanomolar‐level KAN detection (LOD = 0.021 µm) in mild environments containing low levels of natural organic matter (NOM), and maintaining reliable micromolar‐level sensitivity (LOD = 0.37–1.44 µm) in environmentally complex matrices such as synthetic urine, tap water, and NOM‐rich water samples. Given its excellent water solubility, environmental stability, and structural adaptability, PQx‐Ph emerges as a promising candidate for real‐time monitoring of antibiotic contamination. Future integration into portable sensing platforms will broaden its applications in environmental and public health monitoring.